Effect of Dexmedetomidine with or without Midazolam during procedural dental sedation in children: a randomized controlled clinical trial - Amira A. ElKhatib; Tamer A. M. Ghoneim; Karin M. L. Dowidar; Nadia A. Wahba (BMC, 2024)
Abstract Background Dental anxiety is a global problem in the realm of pediatric dentistry. The use of procedural sedation is recommended to avoid substandard or unsafe dental treatment in preschoolers. This study aimed to compare the effect sedation with Dexmedetomidine with or without Midazolam in terms of sedation level, analgesic effect and ease of treatment completion in preschool children. Methods A triple blind randomized controlled clinical trial comprised 72 healthy uncooperative children, 4-6 years old, were randomly allocated into three groups of 24 patients each: Group I patients were sedated with nebulized 5 μg/kg Dexmedetomidine (DEX), Group II with nebulized 3 μg/kg DEX followed by nebulized 0.3 mg/kg Midazolam (MID), and Group III with nebulized 0.5 mg/kg MID. Along the session, the three regimens were assessed and compared during the sedation level (children responsiveness) using the Modified Observer's Assessment of Alertness/Sedation Scale, the analgesic effect using the Face, Leg, Activity, Cry, Consolability scale and ease of treatment completion using a separate 5-point scale. Vital signs were recorded before and during sedation, until full recovery. Results A significant difference was detected regarding children responsiveness during operative procedure in favour of DEX in comparison to MID and DEX/MID groups (P = 0.045). Within the DEX group, a significant difference was recorded regarding children responsiveness at optimum sedation and during the operative procedure (P = 0.04). Although, the analgesic effects of sedative drugs showed no statistically significant difference among the study groups (P = 0.20), the ease of treatment completion was statistically higher in the DEX than MID and DEX/MID groups (P = 0.03). Conclusion Dexmedetomidine provides a moderate level of sedation, that allowed better patient cooperation, and easy completion of performed dental procedures.